Lattice‐Cell Orientation Disorder in Complex Spinel Oxides. Issue 4 (7th November 2016) - Chen, Yan; Cheng, Yongqiang; Li, Juchuan; Feygenson, Mikhail; Heller, William T.; Liang, Chengdu; An, Ke
Abstract : Transition metal (TM) substitution has been widely applied to change complex oxides crystal structures to create high energy density electrodes materials in high performance rechargeable lithium‐ion batteries. The complex local structure in the oxides imparted by the TM arrangement often impacts their electrochemical behaviors by influencing the diffusion and intercalation of lithium. Here, a major discrepancy is demonstrated between the global and local structures of the promising high energy density and high voltage LiNi0.5 Mn1.5 O4 spinel cathode material that contradicts the existing structural models. A new single‐phase lattice‐cell orientation disorder model is proposed as the mechanism for the local ordering that explains how the inhomogeneous local distortions and the coherent connection give rise to the global structure in the complex oxide. Further, the single‐phase model is consistent with the electrochemical behavior observation of the materials. Abstract : A new lattice‐cell orientation disorder model is proposed for the local ordering mechanism. It illustrates how the inhomogeneous local distortions and the coherent connection give rise to the global structure and alter the material functional behaviors in the LiNi0.5 Mn1.5 O4 spinel oxides with variant "ordering" degrees.